RESIDUAL LEVEL OF DELTAMETHRIN INDUCED GASTRITIS AND PREVENTIVE ROLE OF CURCUMIN ON STOMACH MUCOSA - Amna Halima,; Wajid Akbar,; Haider Ali,; Muhammad Junaid,; Imtiaz, Humaira; Sumaira Javed, (Journal of Ayub Medical College Abbottabad, 2023)
Background Benefits of Curcumin for health have been explained by different experimental models and clinical trials. It is a very potent antioxidant. Curcumin was found to play a preventive and curative role in both acute and chronic gastritis. Deltamethrin is a useful pesticide when applied with caution to crops. However, it also has noxious effects on gastric mucosa once ingested with sprayed crops. Its maximum permissible limit, MRL (Maximum Residual Level) as pesticide food residues is 5mg/kg body weight as defined by WHO. However, there is still a potential to cause harm at these levels and may be a serious potential health hazard. The present study aimed to: (a) determine the prevalence and severity of gastritis induced by deltamethrin when administered at MRL doses and (b) To observe the preventive effect on gastric mucosa against the action of Deltamethrin present as a residual pesticide in different vegetables and fruits. Methods In this two-phase subacute toxicity study of seven weeks, forty Sprague Dawley rats were divided into eight subgroups. Control groups were kept on a normal diet and sesame oil. Out of the two treatment groups, one group was given deltamethrin (5mg/kg body weight) orally along with curcumin 100mg/kg body weight. The second group was first given deltamethrin (5mg/kg body weight) and curcumin (200mg/kg). All were culled at its end. The stomach samples were collected and processed to obtain histology slides for analysis via microscopy and micrometry. Grading was done to look for changes according to the Visual Analogue Scale and Operative Link on Gastritis Assessment (OLGA). Results The experimental deltamethrin group when compared to control groups, revealed mild changes in stomach histomorphology while curcumin-treated both groups; Group D (100mg/kg) and Group E (200mg/kg) showed no changes. Conclusion Administration of Deltamethrin even in maximum residual dose (permissible) is proven to be toxic. Curcumin is hence proved to protect the gastric mucosa against the toxic effects of deltamethrin ingested in residual form.